Heavy Metals in Cetraria islandica: Health Risk Assessment - Topal, Murat; Arslan Topal, E. Işıl; Öbek, Erdal; Aslan, Ali (Springer Science and Business Media Deutschland GmbH, 2024)
In this chapter, potential human health risk of the heavy metals associated with usage of Cetraria islandica were evaluated. Heavy metals (lead, cadmium, manganese, chromium, copper, zinc, and nickel) were determined in Cetraria islandica. Highest and lowest heavy metal values were 87 ± 4.3 mg/kg for manganese (Mn) and 0.12 ± 0.01 mg/kg for cadmium (Cd). When potential health risk was assessed, the doses of exposure for man, woman, and child followed the order of bread > tea > dermal. Risk of health for bread and tea were child > woman > man. Also, risk of health for dermal was woman > child > man. Non-carcinogenic risk was woman > child > man for dermal way. Non-carcinogenic risks were child > woman > man for dietary. Highest total hazard index (THI) was 6.33 for chromium (Cr), lowest THI was 0.22 for zinc (Zn). THIs were zinc < copper < cadmium < nickel < lead < manganese < chromium. The THIs were higher than 1 for chromium, manganese and lead. Total highest carcinogenic value was 1.73E?03 for Ni and minimum was 1.19 E?05 for lead. Carcinogenic risks for bread (cadmium, nickel and chromium) were high. As a result, it was determined that Cetraria islandica may cause cancer risk if consumed as additive in bread. It was determined that if Cetraria islandica was consumed as tea and cream, there would be no risk of cancer and could not adversely affect human health. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
Keywords: Cetraria islandica; Exposure; Health risk; Heavy metals; Lichen